Satisfaction and Loyalty of Banking Customers in Indonesia - Nur Azizah; Harry Puspito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Improved customer satisfaction and loyalty are essential metrics in increasing a company's revenue and profit in the banking industry. This research aims to determine the effect of satisfaction on loyalty among bank customers in Indonesia. The study was conducted by face to face interview method (F2F) among 1910 bank customers in eight metropolis in Indonesia (2019). The sampling method used a random sampling followed by a booster sampling approach. The analysis was conducted using the Structural Equation Modeling (SEM) by WarpPLS approach. The results show that satisfaction positively and very significantly affects loyalty.